PENGEMBANGAN INSTRUMEN SIKAP ILMIAH SISWA PADA MATA PELAJARAN IPA: PENDEKATAN EXPLORATORY DAN CONFIRMATORY FACTOR ANALYSIS - Muldayanti, Nuri Dewi; Kurniawan, Arif Didik (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
Scientific attitude is an essential component in science learning, as it supports students’ ability to think critically, engage in scientific processes, and actively participate in learning activities. The purpose of this study was to develop a scientific attitude instrument for junior high school students using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). This research employed a descriptive quantitative approach, in which data and information related to students’ scientific attitudes were collected comprehensively. The collected data were subsequently used to construct a scientific attitude instrument. Data were gathered using a questionnaire as the research instrument. Data analysis techniques involved Exploratory Factor Analysis (EFA) to identify the relationships among manifest variables or indicator variables in forming latent constructs, and Confirmatory Factor Analysis (CFA) to examine whether the indicators grouped according to their latent variables were consistently represented within their respective constructs. The results of the EFA indicated that the scientific attitude instrument consisted of two factors with eigenvalues greater than one, each comprising seven items. Furthermore, the CFA results demonstrated that the constructed model showed a good fit and consistency across both factors. In conclusion, the developed scientific attitude instrument consists of 14 items and can be used to measure students’ scientific attitudes.